Distribution. Restricted to the cooler waters of the N Atlantic Ocean, as far N as the Davis Strait, Jan Mayen, and Spitsbergen, and as far S as NE USA, Azores, and Canary Is; in E Atlantic Ocean, this species appears to be relatively rare S of Bay of Biscay. Although its occurrence seems to be relatively continuous in some parts of its distribution, such as in the E Atlantic Ocean, it appears to be more fragment ed in others, such as in the waters off E Canada. in Ziphiidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. Restricted to the cooler waters of the N Atlantic Ocean, as far N as the Davis Strait, Jan Mayen, and Spitsbergen, and as far S as NE USA, Azores, and Canary Is; in E Atlantic Ocean, this species appears to be relatively rare S of Bay of Biscay. Although its occurrence seems to be relatively continuous in some parts of its distribution, such as in the E Atlantic Ocean, it appears to be more fragment ed in others, such as in the waters off E Canada. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Ziphiidae, pp. 326-357 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 348, DOI: 10.5281/zenodo.6608481